Odd man in : My years in the Indian police - Stracey, Eric (New Delhi, 1981)
This is the third and the last volume of Prakash Tandon's A Punjabi Trilogy. The first volume, Punjabi Century, covered the period, 1857-1947 and the second Beyond Punjab, 1947-1960. Both were widely acclaimed as brilliant pieces of autobiographical writing. This volume begins from 1961 when the author's employer, Unilever, asked him to take over their business in India with all its scattered factories and branches.
Keywords: India-Police